Do coastal fronts influence bioerosion patterns along Patagonia? Late Quaternary ichnological tools from Golfo San Jorge - Richiano, Sebastián Miguel; Aguirre, Marina Laura; Castellanos, Ignacio; Davies, Karen; Farinati, Ester Amanda (Journal of Marine Systems)
Late Quaternary marine molluscan skeletal concentrations from Argentina constitute a remarkable record of variations in palaeoceanographical conditions during interglacial times (mainly ca. 125 ka to present). Particularly, the Golfo San Jorge coastal area represents an extraordinary geographical zone to target from different points of view, mainly due to its linkage between northern and southern Patagonia, characterized by particular and contrasting physico-chemical conditions with direct consequences for littoral marine communities, determining their composition and structure. Among varied biological activities controlled by different environmental factors (i.e., substrate nature, sedimentation rates, water depth, sea surface temperature, salinity, nutrients-productivity), bioerosion traces can provide palaeoenvironmental evidence with important implications for palaeoclimate interpretations. In addition, the application of bioerosion patterns regionally and through time is a recent valuable worthy palaeoenvironmental tool not as yet developed for Patagonia. We attempted to characterize, qualitatively/semiquantitatively, the ichnotaxonomic composition of the coastal area of northern Golfo San Jorge since the Late Pleistocene; to compare results with those obtained for other geographical areas along Patagonia and the Bonaerensian coastal sectors; lastly, to evaluate its palaeoenvironmental/palaeoclimatic significance in a clue area in terms of circulation patterns near the Southern Ocean climatic pump. At Bustamante (Northern Patagonia Frontal System) Domichnia traces were dominant during the Late Pleistocene while Praedichnia in the mid-Holocene. Bustamante exhibits the highest ichnodiversity for the whole Argentinean coastal area. Ichnodiversity is not strongly different between Late Pleistocene and mid-Holocene interglacials and compared to present; however, the relative abundance of some ichnotaxa (e.g., Oichnus, Iramena, Pennatichnus, at Camarones; Oichnus, Iramena, Pinaceocladichnus, at Bustamante) ...